2022
DOI: 10.1136/bmjopen-2022-064436
|View full text |Cite
|
Sign up to set email alerts
|

Choice and Partnership Approach to community mental health and addiction services: a realist-informed scoping review

Abstract: ObjectivesThe Choice and Partnership Approach (CAPA) was developed to create an accessible, child-centred and family-centred model of child and adolescent mental health service delivery that is adaptable to different settings. We sought to describe the state of evidence regarding the extent, outcomes and contextual considerations of CAPA implementation in community mental health services.DesignScoping review.Data sourcesPublished and grey literature were searched using MEDLINE, Embase, CINAHL, PsycINFO, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 48 publications
(189 reference statements)
0
2
1
Order By: Relevance
“…For some, this contributed to engaging in harmful behaviours, such as self-harming and substance abuse. These findings contrast slightly with those of Punton et al (2022) and MacDonald et al (2022) who found that some young people engaged in harmful behaviours in an attempt to be taken seriously by service providers and seen sooner. While any escalation in destructive behaviours is concerning, there is evidence to suggest that young people presenting with severe mental distress, such as self-harming, are more likely to experience shorter wait times than those with less urgent symptoms (Edbrooke-Childs & Deighton, 2020).…”
Section: Worsening Waitscontrasting
confidence: 75%
See 2 more Smart Citations
“…For some, this contributed to engaging in harmful behaviours, such as self-harming and substance abuse. These findings contrast slightly with those of Punton et al (2022) and MacDonald et al (2022) who found that some young people engaged in harmful behaviours in an attempt to be taken seriously by service providers and seen sooner. While any escalation in destructive behaviours is concerning, there is evidence to suggest that young people presenting with severe mental distress, such as self-harming, are more likely to experience shorter wait times than those with less urgent symptoms (Edbrooke-Childs & Deighton, 2020).…”
Section: Worsening Waitscontrasting
confidence: 75%
“…Experiencing long waits between the first and second appointments may reflect the use of specific service models. Within Aotearoa and internationally, many community mental health services implement the Choice and Partnership Approach (CAPA) (Campbell et al, 2022), which is a service improvement model designed to centre the unique needs of each young person seeking help while also effectively managing capacity and demand (Robotham et al, 2010). This usually involves an initial 'choice appointment' to reach a shared understanding of the challenges the young person may be experiencing and to collaboratively explore possible treatment options (Robotham et al, 2010).…”
Section: Hidden Waitsmentioning
confidence: 99%
See 1 more Smart Citation